The Resurgence of Islamic Economic Thought: Contributions of Schools of Thought in Answering Contemporary Economic Challenges - Nur Rahman; Novelika, Lutfiyah Rahma; Mubarok, Alrojak; Pratama, Gigih Yoga (Journal of social Philantrophy and Halal Research, 2024)
Islamic economic thought has regained attention as a potential alternative to addressing various contemporary economic issues. This phenomenon is known as the resurgence of Islamic economic thought. This raises another question: how has Islamic economic thought revived after the 1950s, and what contributions have different schools of thought made in facing contemporary economic challenges? This study employs a literature review method with a descriptive approach. The development of Islamic economics has been marked by the emergence of several schools of thought, categorized into three main groups: the Iqtishaduna School, the Mainstream School, and the Critical Alternative School. These schools remain within the framework of Islam based on the Qur’an and Hadith, enriching Islamic economic knowledge without undermining it. The schools of Islamic economic thought hold great potential to provide fair, ethical, and sustainable solutions to contemporary economic challenges